If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1.6x) + -1.33 = -1x + 4.13 Remove parenthesis around (1.6x) 2 * 1.6x + -1.33 = -1x + 4.13 Multiply 2 * 1.6 3.2x + -1.33 = -1x + 4.13 Reorder the terms: -1.33 + 3.2x = -1x + 4.13 Reorder the terms: -1.33 + 3.2x = 4.13 + -1x Solving -1.33 + 3.2x = 4.13 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -1.33 + 3.2x + x = 4.13 + -1x + x Combine like terms: 3.2x + x = 4.2x -1.33 + 4.2x = 4.13 + -1x + x Combine like terms: -1x + x = 0 -1.33 + 4.2x = 4.13 + 0 -1.33 + 4.2x = 4.13 Add '1.33' to each side of the equation. -1.33 + 1.33 + 4.2x = 4.13 + 1.33 Combine like terms: -1.33 + 1.33 = 0.00 0.00 + 4.2x = 4.13 + 1.33 4.2x = 4.13 + 1.33 Combine like terms: 4.13 + 1.33 = 5.46 4.2x = 5.46 Divide each side by '4.2'. x = 1.3 Simplifying x = 1.3
| 4z+17=3z+4 | | 5-2x-4x=9 | | 27(2/3n) | | 500/3000 | | 7/3xb^4 | | y=-15-(-2)-(11-6) | | 2x^2y+4xy-58y=0 | | y=-20+30-40-(-50) | | (10-y)+y=3.09 | | y=x^3+2x^2-8x-5 | | (9+z)(5z+3)=0 | | 5x^3+40x^2+60x=0 | | Z=23 | | 2x-8+2=x-3+5 | | f(x)=x^3+2x^2-8x-5 | | 4x(2x-1)^1/2 | | n^2-19n+10=0 | | 7(3-z)6=-z | | 1/3x+2=1/6x+4/3 | | 3y=2x+b | | 3(x+7)-2x=3+2x | | Y=x^4-3x^2 | | 28=4b-3s | | -3+5x+30=37 | | 28=4b+3s | | -8(3+r)=32 | | 3/3-4 | | -3(2h+1)=4h-3 | | .15-c=1.105 | | -3(-5)(-7)(-1)= | | -8(3+r)=42 | | 8-3*5+2= |